Research on Radionuclide Diffusion Mechanism in the Ocean and Emergency Response under Oceanic Radioactive Events - Zichao Li; Rongchang Chen; Chen Liu; Qingqing Xue; Zhixia Wang; Tao Zhou (Science and Technology of Nuclear Installations)
On March 11, 2011, a serious radionuclide leakage accident occurred at Fukushima Daiichi nuclear power plant, and a large number of radionuclides were released, causing serious pollution to the ocean environment. On August 25, 2021, Japan announced the overall plan for the discharge of radioactive sewage from the Fukushima Daiichi nuclear power plant into the ocean, and the discharge will begin around the spring of 2023. All operational and under-construction nuclear power plants in China are distributed in coastal areas presently. In case of a nuclear leakage accident, radionuclides will diffuse through the ocean and pollute the ecological environment. The study of radionuclide diffusion mechanism in the ocean and emergency response plays an important role in accident mitigation under oceanic radioactive events. A radionuclide diffusion model in the ocean was established and the radionuclide diffusion mechanism in the ocean was analyzed. And then a prediction and monitoring system of radionuclide diffusion in the ocean was proposed. The results show that the short-term radionuclide diffusion is mainly influenced by the source term, flow field and decay of 131I, and the degree of influence decreases in turn. On the whole, influences of the flow field and 131I decay are weakened during the long-term diffusion. At the same time, the influence of 137Cs decay begins to be obvious and the influence of suspended matter is increasing. The influence of ocean organisms is always small. Problems of scientific prediction and protection were analyzed, and the emergency response scheme was given. It is of great significance to improve the capacity of emergency response for oceanic radioactive events.